Variaciones interanuales del balance hídrico en Teruel - Sánchez Fabre, Miguel (Geographicalia, 2017)
From mean temperatures and rainfall data for the period 1948/49 - 1988/89, an medium hydric balance index card is elaborated. Then, selecting 11 years with differential pluviometric charactenstics, the corresponding hydric index cards are made; these are analysed comparing its data with the ones verified in the original.